Analisis Dampak Pelaksanaan Webinar Terhadap Literasi Keuangan Pada Peserta Webinar Nasional Investasi Saham - Maha Martabar Mangatas Lumbanraja; Rahmat Junaidi; Sri Wahyuni Wildah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
The capital market has been known as an alternative financing and investment in various countries with the presence of the Stock Exchange, but the initial findings from the study show that knowledge of alternative financing and investment (known as Financial Literacy) in developed and developing countries still shows significant differences. The role of Financial Literacy in creating economic growth in a nation is currently being observed by a number of academics, where it is clearly seen that countries with better levels of financial literacy will tend to develop more than countries with lower levels of financial literacy. Indonesia's financial literacy level which is still lower than neighboring countries such as Australia, Malaysia and Singapore in 2014 indicates the need for a number of ways that must be done, one of which is through the role of universities and organizational bodies under them to carry out this educational function. This research was conducted to determine the impact of the implementation of one of the webinars conducted by the Investment Gallery, Riau University with the theme "Getting Profit Equal, Losing Equal Losing: Creating an Investment Literate Generation" which was attended by 340 participants. The research sample used a convenience sampling technique approach and the sample size used King's auxiliary table in order to obtain a sample size of 151 people. Data were analyzed using descriptive statistical approach (percentage and cross tabulation analysis). The results showed that there was an increase in understanding among participants as a result of the holding of the National Stock Webinar, however, there were still participants who did not increase their understanding optimally, so it is advisable to provide further understanding through a series of stock webinar held by the Investment Gallery, Riau University. This study also has limited analysis using Descriptive Statistics techniques which cannot be generalized directly to other populations and it is hoped that this can be the basis for further research through modeling that can be applied directly to other populations